Serum ferritin as a predictive biomarker for PEG IFNα-2b efficacy in chronic hepatitis B treatment - Chen, Meiya; Wang, Chenhao; Lin, Miqiang; Cai, Shiran (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundChronic hepatitis B (CHB) caused by HBV infection leads to persistent liver inflammation. PEG IFNα-2b shows higher functional cure rates than oral antivirals, but identifying optimal candidates remains challenging. This study evaluates serum ferritin as a predictive biomarker for PEG IFNα-2b efficacy.MethodsSerum ferritin, HBsAg and transaminase were monitored in CHB patients treated with PEG IFN α-2b at baseline (0w), 12w and 24w. Patients were divided into the effective group (HBsAg reduction ≥1 log10 IU/mL or clearance) and the ineffective group (HBsAg reduction <1 log10 IU/mL) at 24 weeks. Similarly, for the results at 48 weeks, the patients were divided into the clearance group (achieving HBsAg clearance) and the non-clearance group (not achieving HBsAg clearance). To analyze the correlation between serum ferritin and the decrease of HBsAg, a multivariate logistic regression model was constructed. Potential confounding factors such as age, gender, HBeAg and HBV DNA status, ALT, AST, and iron metabolism indicators (FE, TIBC, TS) were included to evaluate the independent predictive effect of ferritin levels on the therapeutic effectiveness, calculate the corrected OR value and 95% CI. The predictive effect was evaluated by the ROC curve.ResultsAmong patients with chronic hepatitis B (CHB) who completed the PEG IFNα-2b course of treatment, the serum ferritin levels of all patients showed an increasing trend at baseline and during the treatment process, and the serum ferritin level in the effective treatment group (HBsAg reduction ≥1 log10 IU/mL or clearance) was significantly higher than that in the ineffective treatment group. It was confirmed by Spearman’s rank correlation analysis that the serum ferritin level was positively correlated with the decrease in HBsAg. Further analysis through the multivariate logistic regression model revealed that serum ferritin remained an independent predictor of the antiviral efficacy of PEG IFNα-2b. ROC curve analysis indicated that serum ferritin had a high predictive value for the antiviral efficacy of PEG IFNα-2b.ConclusionThe level of serum ferritin is closely related to the anti-hepatitis B virus efficacy of PEG IFNα-2b. It has great potential as a reliable and economical biomarker to guide treatment and optimize treatment strategies.